Pengelolaan Sampah dan Pengenalan Metode Ecobrick pada Warga RT 35 Kelurahan Damai Kecamatan Balikpapan Kota - Fitriani, Yustina; Yorika, Rahmi (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Waste or garbage produced by humans is actually not a problem if humans have a good awareness and understanding of how to manage it. However, in reality, public awareness and understanding of waste and a good waste management system have not yet been realized. The method used in this program is through 2 stages. The first stage is preparation. It is done by observing to identify problems at the location. The second stage is the implementation of programs. At this stage, there are 3 main activities, namely the socialization of good waste management, introduction of the ecobrick method, and working together to clean the environment. The partner of this program is RT 35 Damai Village, Balikpapan District. The implementation of the activities carried out for approximately 12 weeks.The sustainability of this activity has the potential to occur, because the society is very enthusiastic. Their next plan is to make ecobricks that can be used as chairs for gathering. Mutual assistance activities also have a potential to be carried out periodically.